Synopsis: Papua New Guinea household survey on food systems (2018): Initial findings - Schmidt, Emily; Gilbert, Rachel; Holtemeyer, Brian; Rosenbach, Gracie; Benson, Todd (International Food Policy Research Institute, 2019)
This research note provides a description of the survey sample and implementation and reports on initial findings from analysis of the survey data. Our aim is to use this research and evidence to spur a policy dialogue on promoting increased agricultural productivity, enhanced food security, and improved nutrition policies in PNG. Initial survey results show that most of the food consumed by rural households in the sample is produced from households’ own farms, indicating that consumption is closely linked with overall agricultural productivity. Classifying the survey sample by poor and non-poor households, we find that the poor households are not consuming the recommended daily calorie levels, considered necessary for a healthy and productive life. The survey data also suggest that child stunting (29 percent) and wasting (7 percent) are relatively high in the surveyed areas.